Data storage security for cloud computing using elliptic curve cryptography - Buop, George Onyango (University of Cape Town, 2020)
Institutions and enterprises are moving towards more service availability, managed risk and at the same time, aim at reducing cost. Cloud Computing is a growing technology, thriving in the fields of information communication and data storage. With the proliferation of online activity, more and more information is saved as data every day. This means that more data is being stored in the cloud than ever before. Data that is stored online often holds private information – such as addresses, payment details and medical documentation. These become the target of cyber criminals. There is therefore growing need to protect these data from threats and issues such as data breach and leakage, data loss, account takeover or hijackings, among others. Cryptography refers to securing the information and communication techniques based on mathematical concepts and algorithms which transform messages in ways that are hard to decipher. Cryptography is one of the techniques we could protect data stored in the cloud as it enables security properties of data confidentiality and integrity. This research investigates the security issues that affect storage of data in the cloud. This thesis also discusses the previous research work and the currently available technology and techniques that are used for securing data in the cloud. This thesis then presents a novel scheme for security of data stored in Cloud Computing by using Elliptic Curve Integrated Encryption Scheme (ECIES) that provides for confidentiality and integrity. This scheme also uses Identity Based Cryptography (IBC) for more efficient key management. The proposed scheme combines the security of Identity- Based Cryptography (IBC), Trusted cloud (TC), and Elliptic Curve Cryptography (ECC) to reduce system complexity and provide more security for cloud computing applications. The research shows that it is possible to securely store confidential user data on a Public Cloud such as Amazon S3 or Windows Azure Storage without the need to trust the Cloud Provider and with minimal overhead in processing time. The results of implementing the proposed scheme shows faster and more efficient communication operation when it comes to key generation as well as encryption and decryption. The difference in the time taken for these operations is as a result of the use of ECC algorithm which has a small key size and hence highly efficient compared with other types of asymmetric cryptography. The results obtained show the scheme is more efficient, when compared with other classification techniques in the literature.